Peningkatan Hasil Belajar SBK Melalui Metode Pembelajaran Contextual Teaching Learning - Aritonang, Fajar Mangisi (JURNAL PENA EDUKASI, 2018)
Abstract: The purpose of this study is to improve student learning outcomes of class VII-C SMP Negeri 1 Stabat academic year 2017/2018. Intrumen data collector in the form of written test and teacher activation observation sheet in applying Contextual Teaching Learning method (CTL). The results of the study are: (1) In the first cycle found from 32 students of class VII-C obtained 19 people complete learning or about 59.4% and 13 people or about 40.6% unfinished; (2) In the second cycle was found from 32 students of class VII-C obtained 28 people complete learning or about 87.5% and 4 people or about 12.5% unfinished; (3) The result of observation of CTL method implementation by teacher obtained the result in cycle I, the value of 77,38 with the category Skilled enough and in Cycle II, value 92,85 with the category "Highly Skilled. It can be concluded that the appropriate CTL method used in SBK subjects, especially the material "appreciate the local music" is shown by the improvement of student learning outcomes. Keyword: contextual teaching learning, works of music Abstrak: Tujuan penelitian ini untuk meningkatkan hasil belajar siswa kelas VII-C SMP Negeri 1 Stabat kabupaten Langkat TP. 2017/2018. Intrumen pengumpul data berupa tes tertulis dan lembar observasi aktivtas guru dalam menerapan metode Contextual Teaching Learning (CTL). Adapun hasil penelitian tersebut adalah: (1) Pada siklus I ditemukan dari 32 siswa kelas VII-C diperoleh 19 orang tuntas belajar atau sekitar 59,4% dan 13 orang atau sekitar 40,6% tidak tuntas; (2) Pada siklus II ditemukan dari 32 siswa kelas VII-C diperoleh 28 orang tuntas belajar atau sekitar 87,5% dan 4 orang atau sekitar 12,5% tidak tuntas; (3) Hasil observasi penerapan metode CTL oleh guru diperoleh hasilnya pada siklus I, nilai 77,38 dengan kategori Cukup terampil dan pada Siklus II, nilai 92,85 dengan kategori “Sangat Terampil. Dapat disimpulkan bahwa metode CTL tepat digunakan pada mata pelajaran SBK khususnya materi ”mengapresiasi karya musik setempat” ditunjukkan dengan peningkatan hasil belajar siswa. Kata kunci: contextual teaching learning, karya musik